“A bridge that will probably never be crossed”: The discourse of accountability in Judge Persky’s sentencing decision of Brock Turner in The People v. Turner (2016) - Jerca, Ana-Maria (Language and Law / Linguagem e Direito, 2020)
The People v. Turner (2016) exemplies a common leniency towards perpetrators of rape in the courtroom. Despite Turner’s conviction bringing hope that trial proceedings might stop exonerating rapists, Judge Persky’s decision to sentence Turner to only six months in jail shows that the perpetrators can still be somewhat exculpated post factum. This paper conducts a critical discourse analysis of Persky’s sentencing decision, analyzing its intertextual relationships with the victim’s impact statement and the perpetrator’s apology inter alia, emphasizing the systematic minimizations of the victim, Chanel Miller’s, descriptions of Turner’s acts of violence. Finally, I analyze Persky’s evaluation of Turner’s apology to Miller, i.e. that reconciling is “a bridge that will probably never be crossed” because Miller’s insistence that Turner acknowledge that his assault was intentional is an exorbitant request. I conclude that Persky passed a sentence that was consistent with his reformulations of Turner’s actions, which parallels findings from previous research.